Neutrophil Extracellular Traps in the Autoimmunity Context - Bruschi, Maurizio; Moroni, Gabriella; Sinico, Renato Alberto; Franceschini, Franco; Fredi, Micaela; Vaglio, Augusto; Cavagna, Lorenzo; Petretto, Andrea; Pratesi, Federico; Migliorini, Paola; Manfredi, Angelo; Ramirez, Giuseppe A.; et al. (Frontiers in Medicine, 2021)
Formation of neutrophil extracellular traps (or NETs) is a strategy utilized by neutrophils for capturing infective agents. NETs consist in a physical net made of DNA and intracellular proteins externalized from neutrophils, where bacteria and virus are entrapped and killed by proteolysis. Several mechanisms contribute to de-condense nuclear chromatin and extrude nucleosome components from the neutrophil; once outside, DNA and DNA-protein complexes are recognized and presented to B-cells by Toll-like- receptor 9 (TLR9) that activate an immunologic response leading to the formation of IgG2 auto-antibody; in this context, NETs represent an antigenic source for autoimmunity. There is a thin balance between production and removal of circulating NETs from blood that is necessary to avoid unwanted autoimmune reaction to NETs components here including the formation of anti-dsDNA antibodies. Circulating DNases 1 and IL3 are the two crucial enzymes for extracellular DNA removal. Recent studies showed that circulating NETs are increased in Systemic Lupus Erythematosus (SLE) for a functional block of NETs removal mediated by anti-DNase antibodies or, in rare cases, by DNase IL3 mutations. Persistence of free DNA or nucleosome components and oxidized proteins in circulating NETs may represent an important trigger to develop autoimmunity in SLE and be associated with the development of lupus nephritis. Monitoring serum NET levels represent a potential new way to herald the development of renal lesions and has clinical implications. Modulating the balance between NETs formation and removal is one of the objectives of basic research that are aimed to design new drugs for SLE.